Asset management in urban water utilities: Case study in India - Brighu, Urmila (Cranfield University, 2008)
Access to safe and sufficient drinking water and adequate sanitation are now recognized as basic human rights. One Millennium Development Goal is to reduce by half the proportion of people without access to safe drinking water and basic sanitation by 2015. However, ensuring sustainability of existing and new services is considered to be one of the major challenges for the water sector in the years to come. In India, in addition to service expansion, existing water service quality has been observed to be deteriorating over recent years. There is therefore an equally urgent need to address sustainability and improvement of service quality to the presently served population. In this low-income country, where water utilities are unable to recover even the service costs of operations and minor maintenance through user charges, there is a need to determine ways and means to be able to maintain a cost-effective service to consumers. For such a capital intensive service these ways have to include not only the introduction of efficiency measures but also the long-term planning of capital maintenance, that is the maintenance of the fixed assets upon which services depend. Water utilities in high-income countries have been using various fixed asset management techniques to improve asset operational efficiency, to plan capital maintenance and to demonstrate their ability to maintain and improve service to their customers. This study explores the viability of the application of asset management techniques and their potential contribution towards improving water service provision in urban centres in India. Following a literature review, a generic asset management model for a low-income country water utility was developed and then applied in the water utility serving Jaipur, Rajasthan to assess the viability of this adaptation. Having identified strengths and weaknesses during this fieldwork a revised model was proposed, including distinct phases of asset management/data intensity, which could be used as a generic approach in large urban centres in India. Following consultations with prospective users in six States, the study showed that it is feasible to take a first step towards asset management at low cost but this will require a change in the management approach. The study identified lack of relevant data as a key factor influencing an effective and comprehensive application of a generic asset management model. The study concludes that the proposed phased asset management models can contribute to improving serviceability for customers; however the concern that remains is the willingness of the organisation to adapt to the necessary changes.
Keywords: Asset management; India; Urban water utility; Water service